Identifying The Criteria of Designing Augmented Reality for Vocabulary Learning in Primary School - Santosa, Imam; Nurkhamidah, Neni; Wulandari, Rossy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The ease of implementing Augmented Reality in the classroom makes AR as a useful learning medium for educators. AR can be used to be teaching media for vocabulary learning. The purpose of this study was to identify criteria in developing a prototype design for educational games based on AR for teaching English vocabulary for elementary school students. this research will also describe the procedures that are followed in designing the educational game design. This procedure is contained in a process called the successive approximation model (SAM). In order to identify the performance gap of present condition, three categories of questionaries were utilized; the activities used to teach vocabulary, the difficulties in teaching vocabularies, and the need and suggestion on teaching vocabulary. The participant of the study is 24 teachers of primary school in the Area of Jabodetabek. The findings of the research revealed that grammar translation method is the most activities used by teacher which indicated the teacher tranquil in the old method in teaching vocabulary. Moreover, the teachers mostly had difficulties on uninteresting activities and lack motivation by the student in learning vocabulary. Additionally, the result of the study emphasizes the need of criteria in choosing vocabulary inside the Augmented reality-based teaching media for vocabulary learning. There criteria of designing augmented reality for vocabulary learning are the use of approach that actively encourage the student to join the activity, which is communicative language teaching and the content of vocabulary in the augmented reality program based on the control of following measures; Word frequency, Structural value, Universality, Subject range, Definition words, Word-building capacity and Style of primary school level